Variasi Leksikal dalam Tuturan Tokoh Losmen Bu Broto: The Series - Hapsari, Maya Pradhipta; Sariono, Agus; Asrumi, Asrumi (Faculty of Humanities, Diponegoro University, 2025)
The function of language in popular media such as web series is not only as a means of communication, but also as a representation of social, cultural, and inter-character realities. Losmen Bu Broto: The Series depicts the interaction between family members, employees, and guests in the contemporary Javanese society that is increasingly open to the influence of modernization. This study aims to find lexical variations in the speech of the characters of the series using a social dialectology approach. This type of research is qualitative with data in the form of dialogue excerpts containing lexical variations obtained from eight serial episodes, which are collected through observation and recording. Data analysis was carried out with the theory of language variation from Chaer and Agustina (2010) and the theory of social class from Wardhaugh and Fuller (2015). The results of the study found four categories of lexical variations, namely Javanese, professional and modern, slang and expressive, and greeting. These results show that in addition to being a means of communication between characters, the lexical variations in Losmen Bu Broto: The Series also function as a representation of social class and Javanese cultural dynamics in modern society.